2012
DOI: 10.1016/j.actbio.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Titanium phosphate glass microspheres for bone tissue engineering

Abstract: We have demonstrated the successful production of titanium phosphate glass microspheres in the size range of ∼10-200 μm using an inexpensive, efficient, easily scalable process and assessed their use in bone tissue engineering applications. Glasses of the following compositions were prepared by melt-quench techniques: 0.5P₂O₅-0.4CaO-(0.1-x)Na₂O-xTiO₂, where x=0.03, 0.05 and 0.07 mol fraction (denoted as Ti3, Ti5 and Ti7 respectively). Several characterization studies such as differential thermal analysis, degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 42 publications
(36 reference statements)
0
91
0
Order By: Relevance
“…All 29 Si data were externally referenced to kaolinite (d = À92 ppm). Corresponding 31 P MAS NMR data were acquired at 9.4 T using a Bruker DSX-400 spectrometer operating at a characteristic 31 P frequency of 161.44 MHz. Single pulse experiments were implemented using a Bruker 3.2 mm double-air-bearing probe which enabled MAS frequencies of up to 20 kHz; p/4 pulse widths of 1.5 ms and recycle delays of 30 s were common to these measurements.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…All 29 Si data were externally referenced to kaolinite (d = À92 ppm). Corresponding 31 P MAS NMR data were acquired at 9.4 T using a Bruker DSX-400 spectrometer operating at a characteristic 31 P frequency of 161.44 MHz. Single pulse experiments were implemented using a Bruker 3.2 mm double-air-bearing probe which enabled MAS frequencies of up to 20 kHz; p/4 pulse widths of 1.5 ms and recycle delays of 30 s were common to these measurements.…”
Section: 4mentioning
confidence: 99%
“…8,30 Cell culture studies have shown Ti phosphate microspheres provide a stable surface for cell attachment, growth and proliferation. 31 However, there have been no structural studies of melt quench derived Ti-doped bioactive silicate glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, each insert was taken out of the well and the entire insert mesh was carefully cut out from the insert along the edge using a scalpel. The samples were sputter-coated with gold before SEM observation [25].…”
Section: Cell Morphology and Viabilitymentioning
confidence: 99%
“…Titanium is also routinely incorporated into bioactive phosphate glasses to control the solubility and is reported to increase biocompatibility [13][14][15]. Cell culture studies have shown Ti phosphate microspheres provide a stable surface for cell attachment, growth and proliferation [16]. Wakamura et al have also shown that Ti incorporated into HA is bactericidal [17].…”
Section: Introductionmentioning
confidence: 99%